TINGKAT PENGANGGURAN DAN KEMISKINAN DI LUMBUNG PANGAN KABUPATEN SIDRAP - Misbahuddin Misbahuddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study aims to determine the level of unemployment and poverty in the Food Barn Sidrap, which is based on research that has been done found that the magnitude of the population is still poor and the unemployed who live in rural districts Sidrap particular region, making the agricultural sector as a key sector, development, productivity and quality of the agricultural sector is the second thing that must be addressed so that the agricultural sector is a mainstay of overcoming poverty and unemployment in rural areas. Need a comprehensive master plan and road map of the relevant institutions to raise the productivity and quality of the agricultural sector, the area of ​​productive agricultural land that tapers reduce productivity. Agrarian Reform Law to be done. Compensation for productive land transition should correlate to increased agricultural productivity, fertilizer subsidies and other saparodi should improve productivity. Efficient implementation and efektifit should continue to be pursued, productivity and quality of land limitations can be overcome with a budget of Research and Development of Agriculture found the variant products, production systems, marketing, and industrial agriculture. Agricultural investment should be encouraged, importance of agriculture to economic growth, poverty, and unemployment in the district Sidrap, need intensive monitoring for program planning and implementation of agricultural programs by relevant agencies so that timely achievement of the target.